Homeless LGBT+ minority stress - Rodríguez Pérez, José Gabriel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Introduction: LGBT+ youth are at high risk of homelessness in addition to experiencing sexual minorities stress. Objective: to know the perception of stress in homeless LGBT+ minorities in their risk of social exclusion. Methodology: linear probability regression model to determine the marginal effects of the items with the probability of social exclusion risk. The significance of the partial effects and the reliability of the degree of classification from the model are evaluated. Results: different types of LGBT+ minority stress influence the risk of social exclusion. Conclusions: future research should expand the LGBT+ sample to achieve a better understanding of this phenomenon.